Chemical Composition, Pharmacological Activities and Industrial Development of Porphyra sp.: A Review - RAN Zhifang, ZHANG Cuicui, GUAN Renwei, ZHAO Yiwu, ZHANG Yongqing (Shipin Kexue, 2025)
Porphyra sp., an economic red alga used as both food and medicine in China, is rich in polysaccharides, phycobilin, active peptides, polyphenols and other major chemical components. This alga exhibits various pharmacological activities such as immunoregulatory, hypolipidemic, antioxidant, antitumor and anti-thrombotic effects, possessing broad development prospects and high economic value. This article systematically reviews Porphyra sp. from three aspects: chemical composition, major pharmacological activities and the current status of industrial development. It also analyzes problems existing in the Porphyra sp. industry and proposes directions for future research on Porphyra sp. with the aim of providing scientific support for the in-depth development and utilization of Porphyra sp. and more broadly for the high-quality development of this industry.